1
$\begingroup$

How can I prove this. what is the way? im up to the second last line. and i dont actually know how can x * (1 + y) then the y just disappears into x * 1.

x + x * y = x
x + x * y = (x * 1) + (x * y)
          = x * (1 + y)
          = x * 1 [THIS LINE]
          = x

thanks

$\endgroup$
1
$\begingroup$

In Boolean Algebra we have:

\begin{align*} a \cdot b &= \min{(a,b)}\\ a + b &= \max{(a,b)} \end{align*}


So, by the first definition it's obvious that:

$$ x \cdot 1 = \min{(x,1)} = x$$

Since $x \leq 1$.

By the same reasoning:

$$1 + y = \max{(1,y)} = 1$$ since $y \leq 1$.

So you have:

\begin{align*} x + x \cdot y &= (x \cdot 1) + (x \cdot y)\\ &= x \cdot \color{red}{(1 + y)}\\ &= x \cdot \color{red}{1}\\ &= x \cdot 1 = x \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.